2023
DOI: 10.3390/life13030614
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Stem Cell Counting Analysis of the Specific Effects of Cell Culture Medium Growth Factors on Adipose-Derived Mesenchymal Stem Cells

Abstract: A recently described kinetic stem cell (KSC) counting method was used to investigate the stem-cell-specific effects of commercial growth factor supplements used for expanding stem cells in adipose-tissue-derived mesenchymal cell preparations. The supplements were a proprietary growth factor product, a source of fetal bovine serum, two sources of pooled human sera, and two sources of human platelet lysate. KSC counting analyses were performed to monitor effects on the fraction and viability of stem cells in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(31 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…Our analyses establish that the SCF of these tissue cell preparations can vary significantly among donors. The KSC counting method also revealed that, unlike previously described human tissue stem-cell-containing preparations [15,16], including MSC-containing preparations from other sources (e.g., bone marrow and adipose tissue) [13,16], the SCF of some donor aBMSC-containing populations is stable with serial cell culture. This newly discovered property may inform future work to establish more effective biomanufacturing processes for MSCs, as well as other tissue stem cell types, for use in SCTs.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Our analyses establish that the SCF of these tissue cell preparations can vary significantly among donors. The KSC counting method also revealed that, unlike previously described human tissue stem-cell-containing preparations [15,16], including MSC-containing preparations from other sources (e.g., bone marrow and adipose tissue) [13,16], the SCF of some donor aBMSC-containing populations is stable with serial cell culture. This newly discovered property may inform future work to establish more effective biomanufacturing processes for MSCs, as well as other tissue stem cell types, for use in SCTs.…”
Section: Introductionmentioning
confidence: 81%
“…Briefly, 1 × 10 5 cells/well were used to start cultures. Serial cell culture was performed as described previously for KSC counting analyses of MSC-containing tissue cell preparations [13], with the counting of live cells and dead cells at each culture passage based on trypan blue dyeexclusion. Cell counting was performed manually according to well established methods using a hemocytometer slide.…”
Section: Serial Cell Culturementioning
confidence: 99%
See 3 more Smart Citations